Gambaran Skala Kepositifan IgM Salmonella typhi dengan Jumlah Leukosit Pada Penderita Demam Tifoid di RSUD Pasar Rebo Jakarta - Nugroho, Heru Purwanto; Suhara, Intan Ryatni; Fauziah, Prima Nanda; Latifah, Imas (Universitas Mohammad Husni Thamrin, 2024)
Typhoid fever is an acute systemic infectious disease caused by the Gram negative bacterium Salmonella typhi. Typhoid fever is still a global health problem for the world community, especially in developing countries. This study aims to determine thedescription of Salmonella typhi IgM positivity scale in typhoid fever sufferers at Pasar Rebo Jakarta Hospital. Investigations that can be carried out for the diagnosis of typhoid fever are the Salmonella typhi IgM serological test which is performed to detect acute typhoid fever through specific detection of serum IgM antibodies to Salmonella typhi antigen O9 lipopolysaccharide. The results showed that 100 people (59.2%) had positive Salmonella typhi IgM examination results and the normal leukocyte count examination results were 47 people (0.278%). The results of the leukocyte count in typhoid fever patients with leukopenia were 20 people (0.118%), the results of patients with normal leukocytes were 70 people (0.414%) and the results of patients with leukocytosis were 10 people (0.059%). The conclusion obtained in this study was to see the scale of Salmonella typhi IgM positivity with the number of leukocytes in patients with typhoid fever at Pasar Rebo Hospital,Jakarta. Therefore further research is needed with a larger number of samples that can affect the results of the Salmonella typhi IgM examination. Keywords : Typhoid fever, Leukocyte count, IgM Salmonella typhi